Interpretasi Mengenai Keharusan Belajar dan Mengajar dalam Al-Qur’an - Fitriana Yasintha; Nabila Azrilia Syahra; Wismanto Wismanto; Rawdia Tuzahara; Nur Azmi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Islam is basically a religion that requires continuous efforts to acquire knowledge. Muslims are obliged to gain knowledge from birth to death. In educating students, educators have an obligation to provide the best possible learning. In this case, educators can imitate the lessons taught by the Prophet. This article aims to describe the obligation to study according to an Islamic perspective in terms of focusing on the hadith of the Prophet regarding the obligation to study. This can be seen in the Al Quran and Hadith, the type of research used in this research is library research. The results of this research are that the teaching and learning process should be related to the characteristics of Prophetic teaching. Be kind to your students, protect them, motivate them, relate events in the learning process, familiarize yourself with dialogue and mental strategies, and maintain anonymity when criticizing or praising students. So that education remains embedded in the minds of students, we need to apply methods that provide good Uswatun Hasana to students